The training of external tutors of teaching practices in education: design, development and evaluation of an experience - Christian Alexis Sánchez-Núñez; Santiago Ramírez Fernández; Antonio García Guzmán (Universitat Politècnica de València, 2011)
This paper, following a review of the literature that justifies the importance of the external tutor role of teaching practices in university education teachers, shows a training experience had as a main objective the improvement of teaching practices throw a course for external tutors implemented on Faculty of Education and Humanities of Ceuta (University of Granada) with more than 60 teachers (external tutors and academic tutors or supervisors). The formative experience, for 80 hours, combining different training methods (lectures, conferences and workshops) structured in four phases: 1) Reflection on teaching practices today, 2) Conferences and lectures on what and how to improve it, 3) Applying the knowledge to the design of "Welcoming plans for trainee in external centers of Child, Primary and Secondary Education in Ceuta city, and 4) Evaluation of training throw teachers feedback. The results show a high positive reaction from external tutors with the training activity and a quick implementation of process to trainee received by the external centers. There have also been detected others needs and how to approach them to be tackle in future courses for improvement of teaching practices, factors, moreover, also reflected in different tendencies and models analyzed.